2007
DOI: 10.1108/10650750710748496
|View full text |Cite
|
Sign up to set email alerts
|

A multifaceted approach to promote a university repository

Abstract: Purpose -The purpose of this paper is to describe the history of KU ScholarWorks, the University of Kansas' institutional repository, and the various strategies used to promote and populate it. Design/methodology/approach -This paper describes how KU ScholarWorks came into being, and discusses the variety of activities employed to publicize the repository and encourage faculty to deposit their work. In addition, the paper discusses some of the concerns expressed by faculty members, and some of the obstacles en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…Furthermore, Schonfeld and Houseright (2010) discovered in a 2009 survey that less than 30 percent of faculty in U.S. colleges and universities were contributing to IRs. In addition, studies of IRs at several institutions such as Cornell (Davis & Connolly, 2007), the University of Rochester (Foster & Gibbons, 2005), the University of Kansas (Mercer, Rosenblum, & Emmett, 2007), the University of Malaya (Abrizah, 2009), and New Zealand's eight universities (Cullen & Chawner, 2011) also reveal some reluctance on the part of faculty to contribute.…”
Section: Faculty Willingness To Contribute To Institutional Repositoriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Schonfeld and Houseright (2010) discovered in a 2009 survey that less than 30 percent of faculty in U.S. colleges and universities were contributing to IRs. In addition, studies of IRs at several institutions such as Cornell (Davis & Connolly, 2007), the University of Rochester (Foster & Gibbons, 2005), the University of Kansas (Mercer, Rosenblum, & Emmett, 2007), the University of Malaya (Abrizah, 2009), and New Zealand's eight universities (Cullen & Chawner, 2011) also reveal some reluctance on the part of faculty to contribute.…”
Section: Faculty Willingness To Contribute To Institutional Repositoriesmentioning
confidence: 99%
“…The potential benefits to faculty of an IR are the possibility of enhanced professional visibility and increased discovery of their works due to their creative materials being available in an open access resource (Crow, 2002). However, many institutions report that faculty have been slow to embrace the idea of contributing to IRs (Davis & Connolly, 2007;Mercer, Rosenblum, & Emmett, 2007;Abrizah, 2009, Cullen & Chawner, 2011.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive literature on IRs discusses outreach to researchers to recruit content (e.g. Gierveld, 2006;Giesecke, 2011;Madsen & Oleen, 2013;Mercer, Rosenblum, & Emmett, 2007;Nabe, 2010;Troll Covey, 2011). However, focusing outreach on content recruitment for the IR misses an important opportunity to promote OA in general; the IR is simply one tool (Otto, 2016).…”
Section: Outreach To Researchers On Open Access and Scholarly Communimentioning
confidence: 99%
“…Mercer describes University of Kansas institutional repository marketing efforts and mediated article deposit services that resulted in minimal faculty uptake (Mercer, Rosenblum, & Emmett, 2007). Troll Covey (2011) conducted faculty focus groups to determine motivations and barriers to depositing research in their institutional repository and found that the "lack of value-added services [to faculty] presented a significant barrier to deposit."…”
Section: Literature Reviewmentioning
confidence: 99%